Dilemma of African Higher Education Global Partnership on MDGS and SDGs - Ongiti, Orpha (African Journal of Education and Practice, 2024)
Purpose: The concept of global partnership in higher education (GPHE) in relation to Millennium Development Goals (MDGs) and Sustainable Development Goals (SDGS) is a debatable topic in the 21st century. GPHE seldom addressed the MDGs and SDGs. Yet, global GPHE is expected to be a panacea to achieving MDGs and SDGs. The purpose of this study was to determine the kind of global partnerships (GP) existing in some selected accredited universities in the East Africa Community (EAC[1]) and whether they addressed the MDGs and SDGs. Methodology: The Human Capital Theory guided the study purporting that investing in higher education produces a workforce to address global common challenges. Secondary data was collected from five accredited universities' websites, hence analyzed thematically. Findings: The results revealed that the majority (80%) of the universities were engaged in student/faculty exchange (80%), joint research (100%), scholarships (100%), capacity building/training (100%); and that their partnerships barely addressed MDGs and SDGs. Unique Contribution to Theory, Practice and Policy: It is recommended that GPHE should incorporate the component of SDGs in their memorandum of understanding (MoU). Likewise, the EAC may consider establishing a body"”EAC Global Partnership Association"”to monitor and evaluate the implementation of global partnerships geared towards the achievement of SDGs. Overall, this study contributes to the implementation of SDGs by providing empirical evidence, insights, and recommendations for advancing GPHE to produce qualified and skilled workforce to transform the world. This study may trigger researchers to collect primary data to determine the extent to which GPHE includes and produces personnel for the achievement of SDGs.